992 RESULTS OF A PILOT HIV/FRAILTY CLINIC - CAN COMPREHENSIVE GERIATRIC ASSESSMENT BENEFIT FRAIL PEOPLE LIVING WITH HIV?. (14th June 2022) - Morrow, H; Horner, M; Thomson-Glover, R
Abstract: Introduction: Frailty has been recognised among people living with human immunodeficiency virus (HIV) and will become more prevalent in coming years given treatment success (Pathai et al J Gerontol A Biol Sci Med Sci 2014;69:833–842). Assessment of frailty and its common syndromes through comprehensive geriatric assessment (CGA) is routinely delivered by geriatricians and is likely to benefit these patients. We piloted a clinic to assess whether a future service would be beneficial for people living with HIV and frailty. Method: 10 patients from the local HIV service, with suspected frailty, were referred to the Frailty Unit for assessment in May 2021. Each patient was assessed for frailty using the Fried model. They underwent CGA which included medication review, therapy assessment, cognitive assessment, using the Montreal Cognitive Assessment (MOCA), and review by a geriatrician. Results: Seven people attended. Six underwent full assessment and one left prior to undergoing medical review. Patient demographics: all white males; mean age 53 years; mean years since HIV diagnosis 11.3; mean Nadir CD4 count 220.4; four with undetectable viral load and three low level viraemia. Four were classified as frail and three pre-frail. All were multimorbid (mean no. co-morbidities, 7.1). Significant medical issues were identified in four patients requiring further investigation and/or referral to other specialities. Polypharmacy was prevalent (mean no. medications 11.1) and medication adjustments were suggested for all patients. The mean MOCA score was 25.7, with two scoring less than 26 prompting memory service referral. Five patients had ongoing physiotherapy/occupational therapy needs. Conclusion: This pilot demonstrated that a CGA approach to frail patients living with HIV identified significant multimorbidity, polypharmacy, cognitive impairment and therapy needs. This allowed for recommendations to be made to improve medical care, optimise function and improve quality of life. Consequently, a permanent HIV/Frailty service and referral pathway have been developed.